2019
DOI: 10.1071/sh19034
|View full text |Cite
|
Sign up to set email alerts
|

New treatment options for Neisseria gonorrhoeae in the era of emerging antimicrobial resistance

Abstract: Neisseria gonorrhoeae, the causative agent of gonorrhoea, has rapidly evolved from an exquisitely susceptible pathogen into a ‘superbug’ with the capacity to exhibit an extensively drug resistant (XDR) phenotype. The threat of untreatable gonorrhoea now looms on the horizon while the arsenal of effective antimicrobial agents diminishes with time. Ceftriaxone remains the mainstay of first-line therapy as a single agent or as the backbone of a dual therapy regimen. The implementation of new assays to facilitate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Antimicrobials such as lefamulin, 112,113 SMT-571, 114 gepotidacin [115][116][117] and especially zoliflodacin 118-122 must be studied further. 123,124 In conclusion, gonococcal AMR remains a major global public health concern, which compromises treatment and control of gonorrhoea. WHO GASP, including its liaised GASPs, provides invaluable data regarding decreased susceptibility and resistance to therapeutically relevant antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials such as lefamulin, 112,113 SMT-571, 114 gepotidacin [115][116][117] and especially zoliflodacin 118-122 must be studied further. 123,124 In conclusion, gonococcal AMR remains a major global public health concern, which compromises treatment and control of gonorrhoea. WHO GASP, including its liaised GASPs, provides invaluable data regarding decreased susceptibility and resistance to therapeutically relevant antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…70 71 Sitafloxacin may thus be a valuable tool in either dual or monotherapy as a more potent fluoroquinolone. 72 73 However, it faces major hurdles before it could be considered as a treatment for gonorrhea on a global scale. As of 2017, sitafloxacin was only approved in Japan, 74 with one major barrier to approval outside of Asia being the UVA phototoxicity in Caucasian but not Asian subjects.…”
Section: In With the Old…mentioning
confidence: 99%
“…Based on these results, solithromycin cannot be considered noninferior to dual therapy with ceftriaxone plus azithromycin, 80 and this, together with questions around liver hepatotoxicity, have stalled efforts to gain approval. 73 Gepotidacin is the founding member of a class of antibiotics known as the triazaacenaphthylenes and has broad in vitro activity against Gram-positive and Gram-negative organisms, 81 Although gepotidacin, like quinolones, targets type IIA topoisomerases, including DNA gyrase (gyrA) and topoisomerase IV (parC), it binds at a distinct target. 82 In clinical studies, gepotidacin was relatively safe and effective against gonococcus.…”
Section: …As Well As the Newmentioning
confidence: 99%
“…With very little second-line options available, Lewis reviews the search for new agents to manage NG and found that the pipeline is disappointingly sparse. 24 The authors discuss the latest evidence for ertapenem, modern fluoroquinolones (gemifloxacin, sitafloxacin, delafloxacin), solithromycin, gepotidacin and zoliflodacin, though none emerge as a clear winning candidate.…”
Section: Novel Managementmentioning
confidence: 99%